FENOMENA PERNIKAHAN DINI DALAM MEMBINA PENDIDIKAN ISLAM ANAK WARGA WAKAL KECAMATAN LEIHITU KABUPATEN MALUKU TENGAH - Ayustiananda Paila (IAIN Ambon, 2021)
Abstract: The purpose of this study was to describe the phenomenon of early marriage, along with the attitudes of families to early marriage in fostering their children's Islamic education and the causal factors as well as the impact of early marriage in Wakal Village, Leihitu District, Central Maluku Regency. The formulation of the problem in writing this thesis is (1) how is the phenomenon of early marriage (2) how is the attitude of early marriage families towards the Islamic education of their children, (3) the factors that cause early marriage, (4) What are the impacts of early marriage. This study uses a qualitative descriptive research method. Data collection techniques in the form of observation, interviews, and documentation. As well as data analysis techniques in the form of a reduction stage, data presentation, and drawing conclusions. The results showed that there were 3 attitudes from families who married early in children's education, namely (1) entering their children in Islamic institutions such as Islamic boarding schools, TPQ (2) not sending their children to boarding schools, and TPQ (3) the majority of the attitudes of parents themselves did not know the goals and principles of Islamic religious education perfectly. so there is little possibility of realizing educational goals in accordance with Islamic law. There are 3 factors that influence early marriage in Wakal Village, namely (1) low economic level (2) self factor (3) education factor. The impact of early marriage in Wakal Village is divided into 2, namely (1) positive impacts and (2) negative impacts. The positive impacts are (1) can reduce the number of adultery, (2) can ease the burden of life for one or both parties, (3) fortify young people or women from deviation, because marriage can provide opportunities for them to satisfy their sexual needs. Negative Impact (1) social impact, (2) occurrence of domestic violence, (3) psychological impact. Keywords: Early Marriage, Education, Muslim Family Abstrak: Tujuan dari penelitian ini adalah untuk mendeskripsikan fenomena pernikahan dini, beserta sikap keluarga pernikahan dini dalam membina pendidikan islam anaknya dan faktor penyebab juga dampak dari pernikahan dini di Desa Wakal kecamatan leihitu Kabupaten Maluku Tengah. Adapun Rumusan masalah dalam penelitian skripsi ini adalah (1) bagaimana fenomena pernikahan dini (2) bagaimana sikap keluarga pernikahan dini terhadap pendidikkan islam anak-anaknya, (3) faktor-faktor penyebab terjadinya pernikahan dini,(4) Apa saja dampak pernikahan dini. Penelitian ini menggunakan metode penelitian deskriptif kualitatif. Teknik pengumpulan datanya berupa observasi, wawancara, dan dokumentasi. Serta teknik analisis data berupa tahap reduksi, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukan ada 3 sikap dari keluarga yang menikah dini dalam pendidikan anak yaitu (1) memasukan anak-anaknya pada lembaga islam seperti pesantren,TPQ (2) tidak memasukan anaknya ke pesantren,dan TPQ (3) mayoritas sikap orang tua sendiri belum mengetahui tujuan dan prinsip pendidikan agama Islam secara sempurna. jadi sedikit kemungkinan untuk terealisasikan tujuan pendidikan sesuai dengan syari’at Islam. Adapun faktor yang mempengaruhi pernikahan dini di Desa Wakal ada 3 yaitu (1) tingkat ekonomi yang rendah (2) faktor diri sendiri (3) faktor pendidikan. Dampak pernikahan dini di Desa Wakal